Enzyme preparation for catalytically degrading bioplastics and preparation method of enzyme preparation
By developing an enzyme preparation containing enzyme, calcium-based bentonite-loaded nanotitanium dioxide catalyst additive and stable dispersant, the problem of insufficient degradation efficiency and stability of biomass plastic materials has been solved, and the rapid degradation of biomass plastics and the stability of the enzyme preparation system has been achieved.
Patent Information
- Application Number
- CN202510193036.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Biomass plastic materials are still inferior to petroleum-based plastics in terms of mechanical strength and water resistance, resulting in their degradation process and effects being affected by doping or modification of composite materials.
Develop an enzyme preparation that catalytically degrades bioplastics, including enzymes, calcium-based bentonite-supported nanotitanium dioxide catalyst additives, and stable dispersants prepared by aqueous solution polymerization. Through the combination of these components, the degradation efficiency and stability of the enzyme preparation are improved.
This enzyme preparation can accelerate the degradation of bio-based plastics under light conditions, significantly improving the degradation rate, and at the same time improve the stability of the enzyme preparation system, ensuring a continuous and rapid biodegradation effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of enzyme preparations, and in particular relates to an enzyme preparation for catalytically degrading bioplastics and a preparation method thereof. Background Art
[0002] Biomass plastic materials are made from plants or other biological materials as the main matrix. Common biomass plastic raw materials mainly include polylactic acid, starch, polyhydroxyalkanoate, polycaprolactone, etc. They have the advantages of being environmentally friendly and degradable. They can be used in research fields such as medicine, microelectronics and agriculture. They are one of the most promising materials to replace petroleum-based plastic materials. At present, since the mechanical strength or water resistance of biomass plastic materials is still far behind that of petroleum-based plastics, they are usually doped or modified with composite materials to improve their overall performance, but this will have a certain impact on their degradation process and degradation effect. Summary of the invention
[0003] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide an enzyme preparation for catalytic degradation of bioplastics and a preparation method thereof. By adding catalytic additives and stabilizing dispersants, the enzyme preparation is endowed with good degradation efficiency for bio-based plastics and the stability of the enzyme preparation system is improved.
[0004] The purpose of the present invention can be achieved through the following technical solutions: An enzyme preparation for catalytic degradation of bioplastics, comprising the following components by weight: 25-50 parts of enzyme, 1-8 parts of catalytic additive, 2-10 parts of stabilizing dispersant, and 30-50 parts of buffer; The catalytic additive is made by using calcium-based bentonite as a carrier to load nano-titanium dioxide; the stabilizing dispersant is made by introducing polyethylene glycol monoallyl ether into the structure of sodium lignin sulfonate using an initiator through an aqueous solution polymerization method.
[0005] Preferably, the enzyme is one or more combinations of cutinase, alkaline lipase, neutral lipase, protease and laccase.
[0006] Preferably, the buffer is a potassium phosphate buffer with a pH value of 7.2.
[0007] Preferably, the method for preparing the catalytic additive comprises the following steps: A. Take tetraisopropyl titanate and dissolve it in anhydrous ethanol to form a white sol, add concentrated nitric acid dropwise until the white precipitate disappears and a transparent sol is formed, adjust the pH value of the transparent sol to 4-5, and stir continuously at room temperature for 5-6 hours to obtain a transparent yellow sol; B. Calcium bentonite and transparent yellow sol are placed in a reactor, stirred and mixed evenly, aged at room temperature for 20 to 24 hours, and then placed in an oven at 55 to 70° C. for 10 to 12 hours. After drying, the composite material is fully ground; C. Place the composite material in a tubular furnace and calcine it at 270-350° C. for 1.5-3 h in a nitrogen atmosphere to prepare a catalytic additive.
[0008] Preferably, the mass ratio of tetraisopropyl titanate to calcium bentonite is 2-5:1.
[0009] Preferably, the preparation method of the stable dispersant comprises the following steps: (1) Place a sodium lignin sulfonate aqueous solution in a reactor, heat it to 45-55°C, stir it for 20-30 min, then slowly add a potassium persulfate aqueous solution using a constant pressure dropping funnel, heat it to 70-80°C after the addition is complete, slowly add a polyethylene glycol monoallyl ether aqueous solution using a constant pressure dropping funnel after the temperature is constant, continue the reaction for 3-4 h after the addition is complete, add isopropanol to quench the reaction after the reaction is complete, and prepare a crude product; (2) Take isopropanol in a reactor, add the crude product and stir evenly, then let it stand for 2 to 3 hours, remove the supernatant, then filter and separate the precipitated product, add ethanol to the precipitated product and stir it thoroughly, then continue to filter and separate, add methanol to the separated precipitate and stir it thoroughly, stir and let it stand, then filter and separate the precipitate, use acetone and acetic acid as extractants, use a Soxhlet extractor to extract for 4 to 6 hours, and then place it in a vacuum oven at 75 to 85°C and -0.15 to -0.05MPa to dry for 20 to 24 hours to prepare a stable dispersant.
[0010] Preferably, the mass fraction of the sodium lignin sulfonate aqueous solution is 15-25%.
[0011] Preferably, the mass fraction of the potassium persulfate aqueous solution is 1.5-3%.
[0012] Preferably, the mass fraction of the polyethylene glycol monoallyl ether aqueous solution is 18-24%.
[0013] The method for preparing the enzyme preparation for catalytic degradation of bioplastics as described above comprises the following steps: weighing each component by weight, uniformly mixing the catalytic additive, stabilizing dispersant and buffer to obtain a premix, adding enzyme to the premix and stirring to prepare the enzyme preparation for catalytic degradation of bioplastics.
[0014] Beneficial effects of the present invention: The present invention uses calcium-based bentonite as a carrier to load nano-titanium dioxide to prepare a catalytic additive, wherein the nano-titanium dioxide is a common catalytic nano-material in the field of photocatalysis, has a low manufacturing cost and has photocatalytic degradation activity, can generate free radicals under light conditions, and can then trigger an oxidative degradation reaction of bio-based plastics, thereby accelerating the degradation rate of the bio-based plastics, the calcium-based bentonite has ion exchange capacity, and its interlayer cations such as calcium ions can form complexes with enzymes, thereby improving the catalytic activity of the enzymes, and the calcium-based bentonite can adsorb substrates hydrolyzed by the enzymes, making the reaction more thorough and improving the reaction rate, the catalytic additive synergistically prepared by the calcium-based bentonite and nano-titanium dioxide can achieve rapid degradation of biodegradable plastics, and there is a certain gap between the catalytic additive and the bio-based plastics, and these internal gaps can accelerate the invasion of water molecules or enzymes into the bio-based plastic materials, thereby further reducing the degradation cycle of the bio-based plastics. In addition, the present invention utilizes potassium persulfate as an initiator to graft copolymerize sodium lignin sulfonate through an aqueous solution polymerization method, introduces hydrophilic polyethylene glycol monoallyl ether on the phenolic hydroxyl group of the sodium lignin sulfonate, enhances the hydrophilicity of the sodium lignin sulfonate, enables the sodium lignin sulfonate to be better adsorbed on the particle surface of the catalytic additive, makes the particles evenly dispersed in the enzyme preparation system, improves the stability of the enzyme preparation system, and thus ensures that the enzyme preparation is continuously and quickly biodegraded. DETAILED DESCRIPTION
[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Example 1 A method for preparing a catalytic additive comprises the following steps: A. Take 28.4 g of tetraisopropyl titanate and dissolve it in 100 mL of anhydrous ethanol to form a white sol. Add concentrated nitric acid dropwise until the white precipitate disappears and a transparent sol is formed. Adjust the pH value of the transparent sol to 4 and stir continuously at room temperature for 6 h to obtain a transparent yellow sol. B. Take 10g of calcium bentonite and the obtained transparent yellow sol in a reactor, stir and mix evenly, place at room temperature for aging for 24h, then place in an oven at 60°C for drying for 12h, and fully grind after drying to obtain a composite material; C. The obtained composite material was placed in a tubular furnace and calcined at 320° C. for 2 h in a nitrogen atmosphere to prepare a catalytic additive.
[0017] Example 2 A method for preparing a stable dispersant comprises the following steps: (1) Take 50 mL of a 20% sodium lignin sulfonate aqueous solution in a reactor, heat it to 50°C, stir it for 20 minutes, then slowly add 20 mL of a 2% potassium persulfate aqueous solution using a constant pressure dropping funnel, and complete the addition within 30 minutes. After the addition is completed, heat it to 75°C. After the temperature is constant, slowly add 20 mL of a 21% polyethylene glycol monoallyl ether aqueous solution using a constant pressure dropping funnel, and complete the addition within 30 minutes. After the addition is completed, continue the reaction for 3 hours. After the reaction is completed, add 2 mL of isopropanol to quench the reaction to prepare a crude product; (2) Take 500 mL of isopropanol in a reactor, add the obtained crude product, stir evenly, and then let it stand for 2 hours, remove the supernatant, then filter and separate the precipitated product, add 200 mL of ethanol to the precipitated product and stir well, then continue to filter and separate, add 200 mL of methanol to the separated precipitate and stir well, stir and let it stand, then filter and separate the precipitate, use acetone and acetic acid as extraction agents, use Soxhlet extractor to extract for 5 hours, and then place it in a vacuum oven at 80°C and -0.1 MPa to dry for 24 hours to prepare a stable dispersant.
[0018] Example 3 An enzyme preparation for catalytic degradation of bioplastics, comprising the following components in parts by weight: 28 parts of cutinase, 1.5 parts of the catalytic additive prepared in Example 1, 3 parts of the stabilizing dispersant prepared in Example 2, and 30 parts of potassium phosphate buffer with a pH value of 7.2, wherein the cutinase is obtained by expressing yeast and has an enzyme activity of 1000 U / g.
[0019] The preparation method of the enzyme preparation for catalytic degradation of bioplastics comprises the following steps: The components are weighed in parts by weight, and the catalytic additive, the stabilizing dispersant and the potassium phosphate buffer are uniformly mixed to obtain a premix, and cutinase is added to the premix and stirred to prepare an enzyme preparation for catalytic degradation of bioplastics.
[0020] Example 4 An enzyme preparation for catalytic degradation of bioplastics comprises the following components in parts by weight: 35 parts of cutinase, 4 parts of the catalytic additive prepared in Example 1, 5 parts of the stabilizing dispersant prepared in Example 2, and 41 parts of potassium phosphate buffer with a pH value of 7.2, wherein the cutinase is obtained by expressing yeast and has an enzyme activity of 1000 U / g.
[0021] The preparation method of the enzyme preparation for catalytic degradation of bioplastics is the same as that in Example 3.
[0022] Example 5 An enzyme preparation for catalytic degradation of bioplastics, comprising the following components in parts by weight: 44 parts of cutinase, 7 parts of the catalytic additive prepared in Example 1, 8.5 parts of the stabilizing dispersant prepared in Example 2, and 45 parts of potassium phosphate buffer with a pH value of 7.2, wherein the cutinase is expressed by yeast and has an enzyme activity of 1000 U / g.
[0023] The preparation method of the enzyme preparation for catalytic degradation of bioplastics is the same as that in Example 3.
[0024] Comparative Example 1 An enzyme preparation for catalytic degradation of bioplastics, comprising the following components in parts by weight: 44 parts of cutinase and 45 parts of potassium phosphate buffer with a pH value of 7.2, wherein the cutinase is obtained by expressing yeast and has an enzyme activity of 1000 U / g.
[0025] The preparation method of the enzyme preparation for catalytic degradation of bioplastics comprises the following steps: The potassium phosphate buffer and cutinase in parts by weight are stirred and mixed to prepare an enzyme preparation for catalytic degradation of bioplastics.
[0026] Comparative Example 2 An enzyme preparation for catalytic degradation of bioplastics, comprising the following components in parts by weight: 44 parts of cutinase, 7 parts of the catalytic additive prepared in Example 1, and 45 parts of potassium phosphate buffer with a pH value of 7.2, wherein the cutinase is obtained by expressing yeast and has an enzyme activity of 1000 U / g.
[0027] The preparation method of the enzyme preparation for catalytic degradation of bioplastics comprises the following steps: The components are weighed in parts by weight, the catalytic additive and the potassium phosphate buffer are evenly mixed to obtain a premix, cutinase is added to the premix, and stirred to prepare an enzyme preparation for catalytic degradation of bioplastics.
[0028] Performance Testing The enzyme preparations prepared in Examples 3-5 and Comparative Examples 1-2 were subjected to performance testing: a. Melt-blending polycaprolactone at 163°C for 7 minutes, drying to constant weight, preheating the completely dried blended particles on a 180°C hot press for 2 minutes, cold pressing for 10 minutes, and obtaining a blend film with a thickness of about 0.5 mm. The film is then cut into a 1cm×3cm shape and dried to constant weight; b. The cut films were placed in the enzyme preparations prepared in Examples 3-5 and Comparative Examples 1-2, respectively, and oscillated in a 37°C water bath (100 r / min). The films with different degradation times were collected, washed thoroughly, and dried in a 40°C vacuum drying oven to constant weight. The weight loss rate of the films was calculated, and the data results are shown in Table 1.
[0029] Table 1 Test results of sample performance
[0030] As can be seen from the data in Table 1, the enzyme preparations prepared in Examples 3-5 of the present invention have good degradation efficiency for bio-based plastic polycaprolactone, and after 36 hours of degradation, the weight loss rate of the bio-based plastic reaches more than 80%. Wherein no catalytic additive and stable dispersant component are added in Comparative Example 1, and the degradation efficiency measured is worse than that of Examples 3-5, and no stable dispersant component is added in Comparative Example 2, and the growth rate of the measured weight loss rate is lower than that of Examples 3-5, indicating that the addition of a stable dispersant can ensure that the enzyme preparation is continuously and quickly biodegraded, and the weight loss rate measured in Comparative Example 1 under different degradation times is lower than the weight loss rate measured in Comparative Example 2, indicating that the addition of a catalytic additive can improve the degradation efficiency to a certain extent.
[0031] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0032] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. An enzyme preparation for catalytic degradation of bioplastics, characterized in that: The method comprises the following components by weight: 25-50 parts of enzyme, 1-8 parts of catalytic additive, 2-10 parts of stabilizing dispersant, and 30-50 parts of buffer; The catalytic additive is made by using calcium-based bentonite as a carrier to load nano-titanium dioxide; the stabilizing dispersant is made by introducing polyethylene glycol monoallyl ether into the structure of sodium lignin sulfonate using an initiator through an aqueous solution polymerization method.
2. The enzyme preparation for catalytic degradation of bioplastics according to claim 1, characterized in that: The enzyme is one or more combinations of cutinase, alkaline lipase, neutral lipase, protease and laccase.
3. The enzyme preparation for catalytic degradation of bioplastics according to claim 1, characterized in that: The buffer is a potassium phosphate buffer with a pH value of 7.
2.
4. The enzyme preparation for catalytic degradation of bioplastics according to claim 1, characterized in that: The preparation method of the catalytic additive comprises the following steps: A. Take tetraisopropyl titanate and dissolve it in anhydrous ethanol to form a white sol, add concentrated nitric acid dropwise until the white precipitate disappears and a transparent sol is formed, adjust the pH value of the transparent sol to 4-5, and stir continuously at room temperature for 5-6 hours to obtain a transparent yellow sol; B. Calcium bentonite and transparent yellow sol are placed in a reactor, stirred and mixed evenly, aged at room temperature for 20 to 24 hours, and then placed in an oven at 55 to 70° C. for 10 to 12 hours. After drying, the composite material is fully ground; C. Place the composite material in a tubular furnace and calcine it at 270-350° C. for 1.5-3 h in a nitrogen atmosphere to prepare a catalytic additive.
5. The enzyme preparation for catalytic degradation of bioplastics according to claim 4, characterized in that: The mass ratio of tetraisopropyl titanate to calcium-based bentonite is 2-5:
1.
6. The enzyme preparation for catalytic degradation of bioplastics according to claim 1, characterized in that: The preparation method of the stable dispersant comprises the following steps: (1) Place a sodium lignin sulfonate aqueous solution in a reactor, heat it to 45-55°C, stir it for 20-30 min, then slowly add a potassium persulfate aqueous solution using a constant pressure dropping funnel, heat it to 70-80°C after the addition is complete, slowly add a polyethylene glycol monoallyl ether aqueous solution using a constant pressure dropping funnel after the temperature is constant, continue the reaction for 3-4 h after the addition is complete, add isopropanol to quench the reaction after the reaction is complete, and prepare a crude product; (2) Take isopropanol in a reactor, add the crude product and stir evenly, then let it stand for 2 to 3 hours, remove the supernatant, then filter and separate the precipitated product, add ethanol to the precipitated product and stir it thoroughly, then continue to filter and separate, add methanol to the separated precipitate and stir it thoroughly, stir and let it stand, then filter and separate the precipitate, use acetone and acetic acid as extractants, use a Soxhlet extractor to extract for 4 to 6 hours, and then place it in a vacuum oven at 75 to 85°C and -0.15 to -0.05MPa to dry for 20 to 24 hours to prepare a stable dispersant.
7. The enzyme preparation for catalytic degradation of bioplastics according to claim 6, characterized in that: The mass fraction of the sodium lignin sulfonate aqueous solution is 15-25%.
8. The enzyme preparation for catalytic degradation of bioplastics according to claim 6, characterized in that: The mass fraction of the potassium persulfate aqueous solution is 1.5-3%.
9. The enzyme preparation for catalytic degradation of bioplastics according to claim 6, characterized in that: The mass fraction of the polyethylene glycol monoallyl ether aqueous solution is 18-24%.
10. A method for preparing an enzyme preparation for catalytic degradation of bioplastics according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: weighing each component by weight, uniformly mixing a catalytic additive, a stabilizing dispersant and a buffer to obtain a premix, adding an enzyme into the premix and stirring and mixing, and preparing an enzyme preparation for catalytically degrading bioplastics.
Citation Information
Patent Citations
Preparation of nano gel immobilized multienzyme system and application thereof in synthesizing 1,3-propylene glycol
CN101914520A
N-TiO<2> / calcium bentonite composite adsorption catalyst and application thereof
CN108940339A
Cutinase capable of degrading polyester plastic and application of cutinase
CN118006646A
Cited By
Bacterial enzyme mixed preparation for PET plastic degradation and preparation method of bacterial enzyme mixed preparation
CN120738152A
A bacterial enzyme mixed preparation for degrading PET plastic and a preparation method thereof
CN120738152B
Efficient degradation method of refractory plastic based on enzyme catalysis
CN121779783A